2021
DOI: 10.1063/5.0035889
|View full text |Cite
|
Sign up to set email alerts
|

Plume particle energy analysis of an ionic liquid electrospray ion source with high emission density

Abstract: A retarding potential analyser was used to characterise the energy distribution of the plume particles from an electrospray source. The electrospray device uses an ionic liquid, operates at bipolar and relatively high voltages from ±1800 to ±3500 V, and demonstrated ionic emissions with relatively high emission density of more than ±30 µA per emission tip. Electrostatic simulations were used to study the effects of electric field distortion near the grids in the retarding potential analyser, and a correction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…As the sweeping voltage of the retarding grid increases from zero to the acceleration voltage, the normalized collected current first holds steady, then experiences three stages of decline, and finally decreases to zero in both polarities. The overall RPA curves are generally consistent with some other RPA studies of ILISs [25,29,30].…”
Section: Fragmentation Of the Ilissupporting
confidence: 88%
See 1 more Smart Citation
“…As the sweeping voltage of the retarding grid increases from zero to the acceleration voltage, the normalized collected current first holds steady, then experiences three stages of decline, and finally decreases to zero in both polarities. The overall RPA curves are generally consistent with some other RPA studies of ILISs [25,29,30].…”
Section: Fragmentation Of the Ilissupporting
confidence: 88%
“…Correspondingly, the energy efficiency versus the applied acceleration voltage is decreased, though the decrease is relatively slight due to the simultaneous increase of the applied acceleration voltage. A similar trend was mentioned in references [30], though the material of the emitter is different. The voltage loss is probably due to the resistance of the propellant liquid or circuit.…”
Section: Energy Distribution and Voltage Losses Of The Ilissupporting
confidence: 80%
“…36,37 In experiment, droplets could fragment or undergo downstream influences such that droplets reaching the detector may not be those emitted off the jet. 38,39 Note in Fig. 8(b), the total current by modeling lying between those by the experiment 30 and scaling law proportional to a half-power of the flow rate in Eq.…”
Section: B Moderate Conductivity Liquidmentioning
confidence: 80%
“…1 Schematic of the electrospray thruster potential analyzer (RPA) experiments have shown that variations in initial ion emission energy can influence the spacing between the cation-anion pairs. Past a certain energy threshold, the cation and anion molecules may overcome their attractive Coulomb forces, resulting in ion cluster dissociation or fragmentation of downstream solvated ion clusters [24,25]. Furthermore, Gamero-Castaño [26] implemented an Eulerian electrospray beam model based on the line-of-point-charges approach and demonstrated a strong dependence of charged droplet trajectories on their initial velocities.…”
Section: Introductionmentioning
confidence: 99%